ANALISIS KUALITATIF PENGENDALIAN COVID-19 BERDASARKAN KEKUATAN PENTAHELIX DI WILAYAH PARIWISATA KABUPATEN PANGANDARAN - Endang Puji Astuti (Inovasi, 2022)
COVID-19 is not only the responsibility of the health sector but requires collaboration between various sectors. Pangandaran is a tourist location, and a new Regency in West Java requires optimizing the role of Pentahelix to control COVID-19. The purpose of the study was to determine the Pentahelix's role in the implementation of handling COVID-19 in the Pangandaran Regency. The research is qualitative with an in-depth interview technique. The key informants in this study consisted of 50 key informants of leading sectors (Health Department, District Health Laboratory, Hospitals, and Health Centers), cross-sectoral (District, Village), and COVID-19 Task Force. The results showed policy implementation refers to the central policy by issuing Pangandaran Regency Regent Decree Number 443/Kpts.92-Huk/2020 concerning the Task Force for the acceleration of COVID-19 Response. Roles and collaborations have gone well, and all parties taking their respective roles in supporting these efforts. Supporting factors include the issuance of the Regent's Decree, the provision of incentives, and good public understanding. While the inhibiting factors are the lack of human resources, facilities, and infrastructure as well as the negative stigma received by medical personnel and COVID-19 patients, especially at the beginning of the pandemic. Community empowerment activities have been carried out by involving the District and Village level Task Force teams through Village Community Deliberations. The role of the Pentahelix in the implementation of the handling of COVID-19 in Pangandaran Regency, in general, has gone well by the issuance of the Regent's Decree, which becomes the legal force for the implementation of Pentahelix cooperation and collaboration. All parties taking their respective roles in supporting these efforts. Barrier factors in the form of shortages of human resources, facilities, and infrastructure, as well as negative stigma at the beginning of the pandemic, have been reduced, although there are still some that are still obstacles. Empowerment activities through Village Community Deliberations have not been converging on activity plans as village initiatives, so it needed efforts to increase community participation and process initiating of community empowerment. Keywords: Pentahelix, Handling, COVID-19, Pangandaran